The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.3151/jact.9.277
|View full text |Cite
|
Sign up to set email alerts
|

Reinforced Concrete Members Subjected to Cyclic Tension and Corrosion

Abstract: Deterioration process due to corrosion of steel in concrete affects the performance of reinforced concrete structures both in service and ultimate conditions. Corrosion reduces the rebar section, deteriorates the surrounding concrete with the oxides expansion product and it also alters bond between steel and concrete. Moreover, in structures subjected to cyclic loading, the damage due to corrosion can be combined with the mechanical action that is present in service. In this case the initial crack pattern due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 12 publications
1
24
0
Order By: Relevance
“…al. [23], Fischer and Ozbolt [24], Law et al [25]), whereas this is not the case for others that still use very high level of current density (Abosrra et al [26] and Yalciner et al [27]). …”
Section: Electrochemical Corrosion Ratesmentioning
confidence: 95%
See 2 more Smart Citations
“…al. [23], Fischer and Ozbolt [24], Law et al [25]), whereas this is not the case for others that still use very high level of current density (Abosrra et al [26] and Yalciner et al [27]). …”
Section: Electrochemical Corrosion Ratesmentioning
confidence: 95%
“…bridges; the structural analysis of their components cannot be performed without coupling loading with chemical action. At the moment, only a small number of tests, such as those performed by Yoon et al [28], Ballim and Reid [29] and Giordano et al [23], report experimental research on corrosion tests during cyclic loading on RC structures. From the results of these tests it is evident that there is an interaction between load and corrosion which results in disproportionate effects in terms of structural damage.…”
Section: Electrochemical Corrosion Ratesmentioning
confidence: 99%
See 1 more Smart Citation
“…is is the case of existing structures where detailing to enhance ductility and anchorage performance was not completely adequate. In fact, longitudinal cracking caused by corrosion and the progressive loss of confinement exerted by concrete is responsible for a change of behavior for anchorages and overlapping zones and more in general for the transfer mechanism of stresses [16], further exalted if a mechanical action is present [18].…”
Section: Introductionmentioning
confidence: 99%
“…e experimental results by Giordano et al [11] showed that both chemical corrosion and applied cyclic load contributed to the deterioration of RC structural performance. A typical aging RC bridge was investigated by Simon et al [12], and it was found that its seismic resistance and ductility were marginally affected by the corrosion.…”
Section: Introductionmentioning
confidence: 99%